Pengembangan Instrumen Penilaian Berorientasi Higher Order Thinking Skills (Hots) Pada Materi KPK (Kelipatan Persekutuan Terkecil) dan FPB (Faktor Persekutuan Terbesar) - Rambe, Syilvia Cahyani; Sukmawarti (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2023)
This research has two main objectives: (1) to develop an assessment instrument that focuses on higher-order thinking skills (HOTS) in the context of GCD (Greatest Common Divisor) Â and LCM (Least Common Multiple) topics, and (2) to assess the validity of the assessment instrument. This research adopts the Research and Development (R&D) approach, utilizing the 4D model originally introduced by Thiagarajan in 1974. The 4D model consists of four stages: define, design, development, and disseminate. However, in this study, the focus is limited to the first three stages, up to the development stage. The research subjects involve expert validators in the fields of content, assessment, and learning. Data collection is carried out using a questionnaire. The result of this research is the development of an assessment instrument that emphasizes higher-order thinking skills (HOTS) in the context of GCD and LCM topics. The validation by content experts, assessment experts, and language experts has shown that the product is rated as good and highly suitable for use.